Generation of ultra-wide and flat optical frequency comb based on electro-absorption modulator and frequency modulator - 高迪 李培丽 邵茜 陈静远 (Optoelectronics letters, 2016)
An ultra-wide and flat optical frequency comb（OFC） generation scheme using multiple continuous wave（CW） light sources based on electro-absorption modulator（EAM） and frequency modulator（FM） is proposed. In the scheme, each CW light source is broadened and modulated by the first EAM and FM, respectively. The second EAM is introduced to flatten the ultra-wide OFC lines. By setting the wavelength spacing of light sources equal to the bandwidth of sub-OFC, an ultra-wide OFC can be obtained. Principle analysis and simulation for the scheme are performed. The results show that in the case of a single light source, a tunable and flat OFC is obtained. With the increase of light sources, the bandwidth of the generated ultra-wide OFC expands rapidly. In the case of 28 light sources, a 22 GHz ultra-wide OFC with bandwidth of 16.52 THz can be generated.